Plant Extracts as Potential Acaricides for the Management of Red Spider Mite, Oligonychus coffeae Nietner (Acarina: Tetranychidae), in the Tea Ecosystem: An Eco-Friendly Strategy - Deka, Bhabesh; Babu, Azariah; Baruah, Chittaranjan; Sarkar, Suman (Frontiers in Agronomy, 2022)
The effects of the application of aqueous extracts of a selection of five traditional plants (Murraya paniculata, Cassia tora, Amphineuron opulentum, Tithonia diversifolia, and Cassia alata) were compared with that of synthetic acaricide in reducing the population of red spider mite (Oligonychus coffeae), a major tea pest, alongside their impact on natural enemies and green leaf yield. Analysis of large-scale field trials showed that all the five plants extract treatments resulted in similar yield; this was analogous to the application of synthetic acaricide. A reduction in the pest population was observed to be on par with the synthetic acaricide, with a higher number of natural enemies treated using the pesticide-plant-treated plot in comparison to the synthetic acaricide-treated plot, which indicated pesticidal plants had a lower impact on natural enemies. A phytotoxicity study on tea leaves indicated that aqueous extracts of selected plants are non-phytotoxic and do not impart any taint to the prepared tea samples. Therefore, the present investigation outlines how plant extracts used as a botanical pesticide display toxicity against red spider mite on tea plants without harming the beneficial insects, increasing the yield and avoiding any lethal consequence for the tea plants or consumers.